Men, suicide, and family and interpersonal violence: A mixed methods exploratory study. Issue 6 (2nd May 2022) - Fitzpatrick, Scott J.; Brew, Bronwyn K.; Handley, Tonelle; Perkins, David
Abstract: Research has shown a link between gender, violence, and suicide. This relationship is complex, and few empirical studies have explored suicide and family and interpersonal violence perpetrated by men. Drawing on a coronial dataset of suicide cases and a mixed methods design, this study integrated a quantitative analysis of 155 suicide cases with a qualitative analysis of medico‐legal reports from 32 cases. Findings showed different types and patterns of family and intimate partner violence for men who died by suicide. Men used violence in response to conflict, but also to dominate women. Cumulative, interwoven effects of violence, mental illness, alcohol and other drug use, socioeconomic, and psychosocial circumstances were observed in our study population. However, the use of violence and suicidal behaviour was also a deliberate and calculated response by which some men sought to maintain influence or control over women. Health and criminal justice interventions served as short‐term responses to violence, mental illness, and suicidal behaviour, but were of limited assistance.